I.i.19.f Minutes, - Labour Party (Ireland) (1988)
Minutes of the Administrative Council which took place on 25 May 1988 principally concerning: meeting with the Workers Party; report on reorganisation of Dublin West constituency; the militant tendency; national recruitment campaign; and discussion document on the economy. Minutes signed by Mervyn Taylor TD, Party Chair. Also includes: two copies of the agenda; motions on notice; report of the Dublin re-organisation committee on the constituency of Dublin West; text of speech by Dick Spring, Party Leader to the Administrative Council dated 25 May 1988; finance report; policy committee report; report of the International Secretary; list of correspondence received; Labour Youth report; proposal prepared by the national recruitment campaign committee; survey of recruitment circulars; recruitment leaflet proof entitled ‘Sign up with Labour or sign on with the rest’; recruitment leaflet proof entitled ‘Women are talking about’; recruitment leaflet proof entitled ‘Some people say political parties are the same’ But they’ are wrong’; proof recruitment handbook for Party members; and recruitment report prepared by the public relations unit with recruitment leaflet proof entitled ‘cuts hurt!’. (37 pp)